Análise das fontes para a inovação: estudo de caso no mercado de refeições para trabalhadores do Brasil - Lima, Lidia Valéria de Souza (2010)
Innovation is one of the conditions to increase or maintain the competitiveness of organizations. The aim of this study is to identify the sources of innovation in one of the leading foodservices companies in Brazil. The case study methodology was used. This research is organized into Introduction, three chapters and Final Considerations. Chapter 1 presents the concepts of innovation, innovation agent, innovation management and sources of innovation. Chapter 2 explains the methodological procedures and emphasizes that the case presented is revealing, according to the literature criteria. In Chapter 3, the results obtained show that the sources of innovation in the case study are located in both the strategic and operational levels, as a complex phenomenon, which is not possible to analyze by finite models